MALOKLUSI DENGAN MOTIVASI PERAWATAN ORTODONSI PADA SISWA KELAS X SMA N 1 SEWON BANTUL TAHUN 2013 - Bayu Nanang Trianto; Siti Sulastri; Sutrisno Sutrisno (Poltekkes Kemenkes Yogyakarta, 2015)
Based on Survey of National Social Economic 2004 reportedby the Ministry of Health show the general prevalenceof malocclusion and temporo mandibulare junctionin Indonesia has reached 80. Malocclusion is a dentalocclusion shape that deviates from the normal, the deviationof which is crowdeed, caninus ectopik, disto-occlusion,mesio occlusion, crossbite and diastema. Physicalfactors such as tooth abnormalities, or malocclusionsadversely affect the aesthetic appearance, comfort inspeaking or chewing food would affect one’s motivation toperform orthodontic treatment. The results of a preliminarystudy conducted in SMA N 1 Sewon Bantul obtained223 students had cases of malocclusion and 125 studentsexpressed a desire to straighten teeth.The researchpurpose to determine the relationship of malocclusion withorthodontic treatment motivation in class X SMA N 1 SewonBantul in 2013.The kind of this research is observational with cross sectionaldata retrieval. The population in this study were studentsof class X SMA N 1 Sewon Bantul many as 223students. Method of sampling Quota sampling by meansof a population of 30 respondents. Influence variable ofmalocclusion and orthodontic treatment motivation affectedvariables. The technique of collecting data by givingquestionnaires to students and conduct direct examinationirregularities form of malocclusion in students . Thelocation of this study taken in SMA N 1 Sewon Bantul. Statisticaltest using Chi Square test of correlation. The resultsof research conducted on student respondents XSMA N 1 Sewon Bantul obtained with highly motivated studentswith a form of malocclusion crowdeed, ectopiccaninus, disto-occlusion. Chi Square test results malocclusionorthodontic treatment motivation class X SMA N 1Sewon Bantul obtained significantly by 0.010 < á value of0.05, meaning that Ho is refused and Ha accepted. Sothere is a significant or meaningful relationship betweenmalocclusion with orthodontic treatment motivation.There is significant or meaningful relationship betweenmalocclusion with orthodontic treatment motivation in studentsX SMA N 1 Sewon Bantul.